COVID-19-Associated Portal Vein Thrombosis Post-Cholecystitis - Guevara, Sara; Miyara, Santiago J.; Aronsohn, Judith; Homsi, Joseph T.; McCann-Molmenti, Alexia; Mumford, James M.; Keber, Barbara; Shore-Lesserson, Linda; Morales, Luis; Metz, Christine N.; Cho, Young Min; Molmenti, Christine L. Sardo; Loto, Rodrigo; Pesce, Martin M.; Zafeiropoulos, Stefanos; Giannis, Dimitrios; Pipolo, Derek O.; Jacque, Francky; Montorfano, Lisandro; Shinozaki, Koichiro; Shoaib, Muhammad; Choudhary, Rishabh C.; Nishikimi, Mitsuaki; Takegawa, Ryosuke; Endo, Yusuke; Hayashida, Kei; Fontan, Fermin M.; Becker, Lance B.; Molmenti, Ernesto P. (International Journal of Angiology, 2022)
This case study describes a 45-year-old Caucasian male with a past medical history of obesity, hypertension, and non-insulin-dependent diabetes mellitus, who in the setting of coronavirus disease 2019 (COVID-19) pneumonia, developed portal vein thrombosis (PVT) presenting as an acute abdomen after hospital discharge from a cholecystitis episode. PVT is a very infrequent thromboembolic condition, classically occurring in patients with systemic conditions such as cirrhosis, malignancy, pancreatitis, diverticulitis, autoimmunity, and thrombophilia. PVT can cause serious complications, such as intestinal infarction, or even death, if not promptly treated. Due to the limited number of reports in the literature describing PVT in the COVID-19 setting, its prevalence, natural history, mechanism, and precise clinical features remain unknown. Therefore, clinical suspicion should be high for PVT, in any COVID-19 patient who presents with abdominal pain or associated signs and symptoms. To the best of our knowledge, this is the first report of COVID-19-associated PVT causing extensive thrombosis in the portal vein and its right branch, occurring in the setting of early-stage cirrhosis after a preceding episode of cholecystitis.
Keywords: COVID-19; SARS-CoV-2; portal vein thrombosis; acute abdomen; thromboembolic condition